Modelling Population Dynamics for Biodiversity Conservation in Tropical Ecosystemsz - David Ramadi; Afridon; Handri Maika Saputra (Science Journal Get Press, 2025)
This study aims to develop a population dynamics model that supports biodiversity conservation efforts in Indonesia's tropical ecosystems. The study used a quantitative approach based on ecological modelling to develop the model. The model was validated by comparing simulation results with empirical data obtained from field surveys. The results show that factors such as population growth, mortality rates, species distribution, extinction risk, and the effects of climate change have significant impacts on the sustainability of key species, including orangutans, helmeted hornbills, clouded leopards, Sumatran tigers, and tropical corals. In addition, the results of this study can also serve as a basis for more integrated conservation policy planning, both at the national and international levels.